The Relationship Between Smartphone Use and Children’s Emotional Development and Communication Skills at Melati Indah and Bunda Sayang Amanda Early Childhood Education Centers in Jambi, as Examined From an Islamic Perspective - Denny Novitasari (PT Publikasiku Academic Solution, 2026)
Excessive gadget use in early childhood has become an increasing concern because it may interfere with children's emotional regulation and communication development. This study aimed to examine the relationship between gadget use and children's emotional development and communication skills at PAUD Melati Indah and PAUD Bunda Sayang Amanda in Jambi, while also reviewing the findings from an Islamic perspective. This research used an analytical descriptive design with a cross-sectional approach involving 102 children aged 3–5 years. Data on gadget use and emotional development were collected through parent questionnaires, while children's communication skills were assessed using the Peabody Picture Vocabulary Test (PPVT). The data were analyzed using univariate analysis and chi-square tests. The results showed that 56% of children had high-intensity gadget use, 77% experienced emotional problems, and 56% had low communication skills. Statistical analysis confirmed a significant relationship between gadget use and emotional development (p = 0.001), as well as between gadget use and communication skills (p = 0.001). These findings indicate that excessive gadget exposure may contribute to emotional and communication difficulties in early childhood. From an Islamic perspective, gadget use is permissible when beneficial, but must be limited and supervised to prevent harm. Therefore, parents and educators should strengthen guidance, direct interaction, and balanced digital use.